(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to compare the nutrient management practices along with the application of novel fytovita on the plant height of brinjal. Materials and Methods: The experimental land area was 570×330 cm. NPK along with water spray was used as a control group. Foliar application with NPK fertilizers was used as an experimental group. The plant height was measured from the lower cotyledonary node to the growing tip using a ruler. The sample size for each group was 20 and the total sample size was 40. The G-power is 80% with a threshold value of 0.05, and a confidence interval at 95%. Results: From this study, the result shows that treatment T2 has the highest mean value for plant growth of 53.26 cm on 60 DAT. Treatment T1 showed the lowest mean value for plant growth of 37.19 cm. Conclusion: The comparison of nutrient management practices along with the application of novel fytovita on plant height was experimentally studied and novel fytovita as foliar application increased the plant height. The independent sample t-test was done which revealed that both the groups are statistically significant with a p-value 0.020 for plant height on 60 DAT.